2009
DOI: 10.1177/0969733008097990
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Moral Distress and the Paediatric Intensive Care Team

Abstract: A summary of the existing literature related to moral distress (MD) and the paediatric intensive care unit (PICU) reveals a high-tech, high-pressure environment in which effective teamwork can be compromised by MD arising from different situations related to: consent for treatment, futile care, end-of-life decision making, formal decision-making structures, training and experience by discipline, individual values and attitudes, and power and authority issues. Attempts to resolve MD in PICUs have included the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
0
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 71 publications
(109 reference statements)
2
65
0
14
Order By: Relevance
“…12,13 Several qualitative studies on nurses have demonstrated that moral distress is associated with provision of treatments perceived to be overly aggressive and non-beneficial to patients. 10,14,15 While there have been theoretical discussions on moral distress experienced by physicians, there have only been a small number of empirical studies demonstrating moral distress in U.S. physicians, the majority of which have focused on physicians as members of larger interdisciplinary teams. 12,16,17 To our knowledge, there are no studies that describe the physician or physician trainee experience surrounding moral distress associated with end of life care in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Several qualitative studies on nurses have demonstrated that moral distress is associated with provision of treatments perceived to be overly aggressive and non-beneficial to patients. 10,14,15 While there have been theoretical discussions on moral distress experienced by physicians, there have only been a small number of empirical studies demonstrating moral distress in U.S. physicians, the majority of which have focused on physicians as members of larger interdisciplinary teams. 12,16,17 To our knowledge, there are no studies that describe the physician or physician trainee experience surrounding moral distress associated with end of life care in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…In general, most studies suggest that moral distress makes a big impact on the lives of the nursing professionals. Qualitatively, feelings of anger and sadness are the most cited ones in the literature as psychosocial effects caused by moral distress -introspection being the main characteristic (10) .…”
Section: Moral Distress In Nursing Practicementioning
confidence: 99%
“…1 Moral distress after clinical encounters, along with moral dilemmas, has been implicated in emotional distress, unsafe or poor-quality patient care, reduced job satisfaction, and attrition in nursing. [2][3][4][5][6] An extensive literature identifies the ''difficult'' patient and common characteristics and behaviors that compromise the therapeutic relationship, such as social class, occupation or employment status, appearance, age, cleanliness, and attire. [7][8][9][10][11] Previous studies confirm the characterizations of difficult patients and, more broadly, difficult clinical encounters.…”
Section: Introductionmentioning
confidence: 99%